The role of maternal health beliefs in prevention of preschoolers' obesity - Effat Hatefnia; Parvin Azizi; Mostafa Qorbani; Ali Safari-Moradabadi (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Childhood obesity is one of the most serious global public health challenges of the 21st century, affecting every country in the world. Mothers' beliefs and perceptions about their children's obesity and overweight are key to obesity prevention. Given the importance of this issue, the present study aimed to determine perceptions and beliefs of mothers' nutritional behaviors related to overweight preschool children. MATERIALS AND METHODS: This cross-sectional study was conducted on 350 mothers of preschool children with health records who were referred to child health assessment centers. The data collection tool was a researcher-made questionnaire based on the health belief model. SPSS19 was used for data analysis. P < 0.05 was considered significant. RESULTS: The participants (350) included 52% 25-36 years old, and 57.3% live in rural areas. There was a significant difference in the mean perceived susceptibility between mothers with obese children and normal-weight children (P < 0.05). There was a significant positive relationship between severity and perceived benefits and a significant negative relationship with mothers' knowledge. There was also a significant negative relationship between self-efficacy and perceived barriers (P > 0.05). CONCLUSIONS: The results of this study showed that maternal health beliefs were effective in the formation of obesity prevention behaviors in children. In this regard, educational interventions can play an important role in the proper practice of such behaviors.